Analysis of Learning Styles in Clinical Simulation Environments in Students of the Cardio-Respiratory Therapy Program at Universidad Manuela Beltrán 2021. - Gutierrez Gonzalez, Diego Alejandro
This study was designed with the objective of analyzing learning styles in the clinical simulation environment among students of Cardio-Respiratory Therapy at Universidad Manuela Beltrán in the year 2021. Likewise, determinants in the learning processes were identified, along with the learning style that is most in line with clinical simulation and with students in the Cardio-Respiratory Therapy program at Universidad Manuela Beltrán in 2021. To achieve this goal, a questionnaire survey was conducted using the Google platform and the VARK instrument. The population for this research consists of students in the Cardio-Respiratory Therapy program at UMB. The results showed that out of 94 surveyed students, 61.7% (n=58) have a kinesthetic learning style that aligns with the needs of clinical simulation. This learning style is characterized as slow but faster compared to others.